Verification of the method for prediction of the equivalent level of freely flowing traffic noise - MAKAREWICZ, R.; JARZĘCKI, J. (Archives of Acoustics, 1980)
The evaluation of the "acoustic climate" near transport routes, using the numerical method is possible only when we know the values of the parameters describing single noise sources and those of the parameters connected with the attenuating properties of the area adjacent to the route. The paper presents a method for determining these parameters. Direct measurements of the equivalent level were also made. Good agreement between measurement results with values calculated according to the present analytical and theoretical method shows its correctness and thus its usefulness for the problem of shaping the acoustic environment near roads with freely flowing traffic.